2021
DOI: 10.1016/j.jbc.2021.101108
|View full text |Cite
|
Sign up to set email alerts
|

Activity-dependent release of phosphorylated human tau from Drosophila neurons in primary culture

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…By TIRF microscopy, we observed a depletion of Tau in the cytoplasm upon the fusion of VAMP8-positive vesicles with the plasma membrane (Pilliod et al, 2020). Other proteins involved in the endocytic pathways such as Bin1 and the two SNAREs, syntaxins 6 and 8 also contribute to Tau secretion (Glennon et al, 2020;Lee et al, 2021). It seems possible that each of these pathways could permit the release of a specific set of Tau forms.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…By TIRF microscopy, we observed a depletion of Tau in the cytoplasm upon the fusion of VAMP8-positive vesicles with the plasma membrane (Pilliod et al, 2020). Other proteins involved in the endocytic pathways such as Bin1 and the two SNAREs, syntaxins 6 and 8 also contribute to Tau secretion (Glennon et al, 2020;Lee et al, 2021). It seems possible that each of these pathways could permit the release of a specific set of Tau forms.…”
Section: Discussionmentioning
confidence: 87%
“…Interestingly, polymorphisms associated with Bin1 is the second largest genetic risk for sporadic AD (Lambert et al, 2013;Vardarajan et al, 2015). Syntaxins 6 and 8, two SNAREs that play an important role in the membranes trafficking, can interact with Tau C-terminal and increase its secretion (Lee et al, 2021). Syntaxin 6 is found at the trans-Golgi network and early endosomes whereas syntaxin 8 is localized on recycling and late endosomes (Jung et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracellular activity was measured in control and L435F hCSs at baseline, and the L435F hCSs showed significantly reduced activity ( Figure 7 B). To promote neuronal activity, hCSs were treated with KCl, as KCl has been shown to depolarize neurons and increase activity ( Ismael et al., 2021 ). After treatment with KCl, we found the L435F hCSs continued to show reduced levels of extracellular activity ( Figure 7 B).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with our results, it has been demonstrated that intracellular tau was phosphorylated at AT270 (T181), AT100, and PHF-1 in Hela cells (Plouffe et al, 2012). In addition, our recent findings showed that AT8 and AT180 pSites were less phosphorylated inside the cell in Drosophila primary neuronal culture (Ismael et al, 2021). However, Plouffe et al (2012) claimed that intracellular tau at AT8 and AT180 sites was phosphorylated.…”
Section: Discussionmentioning
confidence: 98%